Inflammatory Related Reactions in Humans and in Canine Breast Cancers, A Spontaneous Animal Model of Disease - Tricarico, Domenico; Convertino, Anna Sara; Mehmeti, Irsida; Ranieri, Girolamo; Leonetti, Francesco; Laface, Carmelo; Zizzo, Nicola (Frontiers in Pharmacology, 2022)
Inflammatory cells are emerging markers in various cancers in human trials. The relationship between the inflammatory cells response, cancer grade, and progression has been investigated experimentally in a spontaneous canine model of breast cancer and in the unselected population (18–64 years.o.) under anti-HER2 treatments that represent the most prevalent population in this cancer type. The canine data (N samples = 101) were collected retrospectively for diagnosis in our regional area and evaluated by immunohistochemistry and haemato-chemistry. The inflammatory and immune-related adverse reactions (ADR) in humans were evaluated using EudraVigilance. The “Proportional Reporting Ratio” (PRR) of the mabs was calculated for each ADR with values >2 indicative of high risk. In dogs, we found elevated immunostaining of CD68-macrophages in the lymph node of the aggressive cancer G3 and infiltrating CD20+-lymphocyte. A high density of CD20 + lymphocytes was observed in G1 and a decrease in the density was observed with the histological degree of the tumors. The animals with the sample in G1 showed reduced serum platelet and neutrophil count and elevated lymphocytes and the opposite in severely affected animals. Inflammatory reactions with edema, skin reactions, extravasation, loss of effectiveness, and platelet count decrease (PRR > 13) were found with trastuzumab emtansine in humans, in the absence of immune system reactions. Trastuzumab i.v.-s.c. showed immune system reactions, loss of effectiveness, intolerances with drug withdrawal, technological issues (PRR > 7), and neutrophil count decrease reports. These reactions were less frequently reported for pertuzumab i.v. Case reports of platelet and neutrophil count decrease were not associated with disease progression with a better outcome in humans as in canine breast cancer. Therefore, infiltrating CD68-macrophages are associated with G3, while infiltrating CD20+ and elevated serum lymphocytes in parallel with reduced platelet and neutrophil count play a favorable role in human and canine breast cancer.